Preparation method of integrated positive electrode and gel electrolyte and integrated positive electrode and gel electrolyte

Through the use of integrated positive electrode and gel electrolytes in solid -state lithium -ion batteries, the problem of insufficient contact area of ​​solid electrolytes and electrode contact area is significantly reduced, the interface impedance is significantly reduced, the battery performance is improved, and it is suitable for industrialized applications.

CN115000506BActive Publication Date: 2025-01-28SICHUAN UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202210704805.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-21
Publication Date
2025-01-28
Estimated Expiration
2042-06-21

AI Technical Summary

Technical Problem

In existing solid-state lithium-ion batteries, solid-solid contact between the solid electrolyte and the electrode leads to insufficient effective contact area, which seriously hinders ion migration, resulting in excessive internal resistance of the battery and unsatisfactory battery performance.

Method used

Adopt a preparation method of an integrated positive electrode and gel electrolyte. By synthesizing the skeleton skeleton in situ in situ in order of lithium iron phosphate, and filling the organic monomer into the pores of the gas gel, the optical catalytic aggregation reaction is passed Make organic monomer cross -cross, form an integrated positive electrode and gel electrolyte with silicon dioxide gel as the skeleton.

Benefits of technology

The contact area of ​​the electrode and the electrolyte is greatly increased, the interface impedance is reduced, from 600 ohm to 300 ohm, which improves the performance of solid lithium -ion batteries, solves the problem of solid electrolyte interface contact, and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115000506B_ABST
    Figure CN115000506B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing an integrated positive electrode and gel electrolyte. It comprises the following steps: S1, preparing a lithium iron phosphate positive electrode; S2, synthesizing a silica aerogel skeleton in situ on the lithium iron phosphate positive electrode to obtain a positive electrode material covered with silica aerogel; S3, filling an organic monomer into the pores of the silica aerogel, using ultraviolet light to cause the organic monomer to undergo a photocatalytic polymerization reaction, and after the organic monomer is polymerized and cross-linked, the lithium iron phosphate positive electrode and the silica aerogel skeleton are wrapped to obtain an integrated positive electrode and gel electrolyte with the silica aerogel as the skeleton. The integrated positive electrode and gel electrolyte obtained by the present invention greatly increase the contact area between the electrode and the electrolyte, reduce the interface impedance, improve the performance of the solid-state lithium-ion battery, truly solve the interface contact problem of the solid electrolyte, and can be industrially produced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of solid-state lithium-ion batteries, and in particular to a method for preparing an integrated positive electrode and a gel electrolyte. Background Art

[0002] Lithium-ion battery is a rechargeable battery that mainly relies on the movement of lithium ions between the positive and negative electrodes to work. + Insertion and deinsertion back and forth between the two electrodes: During charging, Li + It is released from the positive electrode and embedded in the negative electrode through the electrolyte, and the negative electrode is in a lithium-rich state; the opposite is true during discharge. Currently, commercial lithium-ion batteries usually use liquid electrolytes, which may cause lithium dendrites to pierce the diaphragm and cause short circuits during use. In addition, liquid electrolytes are also prone to leakage after the battery shell is damaged, and the organic solvents in them are extremely prone to fire and explosion at high temperatures.

[0003] With the research and development of lithium-ion batteries, solid-state lithium-ion batteries have emerged. Solid-state lithium-ion batteries are assembled with solid electrolytes and electrodes, which have stronger safety. The superior mechanical properties of solid electrolytes can effectively resist external pressure and lithium dendrite penetration. In addition, solid-state lithium-ion batteries can reduce the requirements for battery auxiliary components, effectively reduce battery thickness and volume, and improve energy density. In addition, solid electrolytes have excellent electrochemical stability and mechanical properties, and can be matched with various electrode materials. Therefore, the development of high-performance solid electrolytes is an important direction for the development of energy storage components. A major problem that currently hinders the application of all-solid-state batteries is the interface contact problem between solid electrolytes and electrodes. Liquid electrolytes can construct smooth ion migration paths between positive and negative electrodes due to their good wetting ability with organic solvents. There is solid-solid contact between solid electrolytes and electrodes, and the effective contact area is insufficient, which seriously hinders ion migration, resulting in excessive internal resistance of the battery and unsatisfactory battery performance. At present, the methods to solve the contact problem between solid electrolytes and electrodes include surface modification of electrode particles, adding binders with ion transmission capabilities during electrode preparation, adding a small amount of liquid electrolyte or ionic liquid at the interface between solid electrolyte and electrode, etc. These solutions are uncertain and do not really solve the interface problem of solid electrolytes, making them difficult to apply on a large scale in industrial production.

[0004] In the Chinese patent with application number "CN202111376133.5" and patent name "An integrated solid electrolyte-positive electrode assembly and its preparation method and application", it is proposed that the positive electrode sheet and the solid electrolyte sheet are pressed to form an integrated assembly, and the plastic crystal electrolyte added in the positive electrode sheet and the solid electrolyte sheet is used as the interface lithium conductive phase to bond the positive electrode and the electrolyte into one. The first solid electrolyte and the second solid electrolyte independently include one or more of lithium lanthanum zirconium oxide, lithium lanthanum titanate, lithium aluminum titanium phosphate, lithium aluminum germanium phosphate, lithium aluminate, tantalum-doped lithium lanthanum zirconium oxide, niobium-doped lithium lanthanum zirconium oxide, lithium germanium phosphorus sulfur and lithium phosphorus sulfur. The first plastic crystal electrolyte and the second plastic crystal electrolyte independently include organic dinitrile compounds and lithium salts; the organic dinitrile compounds include one or more of succinonitrile, adiponitrile and glutaronitrile; the lithium salt includes one or more of lithium bis(trifluoromethanesulfonyl imide), lithium tetrafluoroborate, lithium trifluoromethanesulfonate, lithium difluorooxalatoborate and lithium dioxalatoborate; the mass ratio of organic dinitrile substances and lithium salts in the first plastic crystal electrolyte is 10: (0.5-5); the mass ratio of organic dinitrile substances and lithium salts in the second plastic crystal electrolyte is 10: (0.5-5). The pressure of the first pressing is 100-600MPa, and the time of the first pressing is 10-1000min; the pressure of the second pressing is 100-600MPa, and the time of the second pressing is 10-1000min, and the temperature of the second pressing is 60-100°C. This process is obtained by pressing, which has high requirements on equipment and cannot really solve the interface contact problem between the electrode and the electrolyte.

[0005] In the Chinese patent with application number "CN202111228453.6" and patent name "A solid electrolyte-electrode integrated diaphragm and its preparation method", the disclosed method includes: adding a thickener to a solvent to obtain a viscosity solution; dissolving an inorganic ceramic powder in the viscosity solution to obtain a suspension; mixing a binder and a dispersant with the suspension to obtain a coating slurry; applying the coating slurry to the surface of the pole piece, and then drying to obtain an aqueous coated electrode supporting inorganic diaphragm; wherein the inorganic ceramic powder includes at least one of LLTO, LATP and LLZO; using non-flammable inorganic components to improve lithium battery safety, improve the heat resistance and mechanical properties of the diaphragm, enhance the absorption and liquid retention performance of the diaphragm, use solid electrolytes, improve ionic conductivity, reduce battery internal resistance, no diaphragm is required, and the preparation is simple. The disadvantages of this process are as follows: after drying, there will be large gaps inside the electrolyte, the impedance is large, and the battery performance obtained is poor.

[0006] The applicant has found that the prior art has at least the following technical problems:

[0007] 1. In the solid-state lithium-ion battery in the prior art, there is solid-solid contact between the solid electrolyte and the electrode, and the effective contact area is insufficient, which seriously hinders the ion migration, resulting in excessive internal resistance of the battery and unsatisfactory battery performance;

[0008] 2. The solid-state lithium-ion batteries in the prior art adopt methods such as modifying the surface of electrode particles, adding a binder with ion transmission ability during the electrode preparation process, adding a small amount of liquid electrolyte or ionic liquid at the interface between the solid electrolyte and the electrode, etc. These solutions are uncertain and cannot really solve the interface contact problem of the solid electrolyte, and are difficult to be applied on a large scale in industrial production. Summary of the invention

[0009] The purpose of the present invention is to provide a method for preparing an integrated positive electrode and a gel electrolyte, so as to solve the technical problem that in the prior art solid-state lithium-ion batteries, there is solid-solid contact between the solid electrolyte and the electrode, the effective contact area is insufficient, ion migration is seriously hindered, the internal resistance of the battery is too large, and the battery performance is not ideal.

[0010] To achieve the above object, the present invention provides the following technical solutions:

[0011] The present invention provides a method for preparing an integrated positive electrode and gel electrolyte, comprising the following steps:

[0012] S1. preparing a lithium iron phosphate positive electrode;

[0013] S2, in situ synthesizing a silica aerogel skeleton on the lithium iron phosphate positive electrode to obtain a positive electrode material covered with silica aerogel;

[0014] S3. Filling organic monomers into the pores of silica aerogel, using ultraviolet light to cause photocatalytic polymerization of the organic monomers, and after the organic monomers are polymerized and cross-linked, wrapping the lithium iron phosphate positive electrode and the silica aerogel skeleton to obtain an integrated positive electrode and gel electrolyte with the silica aerogel as the skeleton.

[0015] Furthermore, in step S1, the steps for preparing the lithium iron phosphate positive electrode are specifically as follows:

[0016] S11, sieving the lithium iron phosphate powder with a sieve to remove lithium iron phosphate particles with large particle sizes, and then drying the lithium iron phosphate powder obtained after the sieving until it is completely dehydrated;

[0017] S12, prepare lithium iron phosphate pole piece, and use PVDF or sodium alginate as adhesive:

[0018] ① When using PVDF as a binder to prepare lithium iron phosphate pole pieces

[0019] PVDF is configured into an NMP solution of PVDF, and the solution is mixed with the lithium iron phosphate powder and Ketjen black dried in step S11 in a ball mill to obtain a positive electrode slurry after ball milling; aluminum foil is spread on an adjustable automatic coater, the positive electrode slurry is poured on the aluminum foil, and the slurry is evenly scraped on the aluminum foil using a scraper, and the thickness of the positive electrode slurry coating is adjusted to 100-400 microns according to the height of the scraper. After scraping, it is transferred to a vacuum oven for drying; after drying, the dried electrode piece is taken out and cut into discs to obtain a lithium iron phosphate positive electrode with a binder of PVDF; the electrode piece cut into discs is weighed, and the active material loading is calculated for standby use;

[0020] ② When using sodium alginate as a binder to prepare lithium iron phosphate electrodes

[0021] Prepare a sodium alginate solution with sodium alginate, mix it with the lithium iron phosphate powder and Ketjen black dried in step S11 in a ball mill, and obtain positive electrode slurry after ball milling; spread aluminum foil on an adjustable automatic coater, pour the positive electrode slurry on the aluminum foil, use a scraper to evenly scrape the slurry on the aluminum foil, adjust the thickness of the slurry coating by 300-600 microns according to the height of the scraper, and dry after the scraping is completed; take out the dried electrode sheet after drying and cut it into discs to obtain a lithium iron phosphate positive electrode with sodium alginate as the binder; weigh the electrode sheet cut into discs, and calculate the active material loading for later use.

[0022] Furthermore, in step S11, a 450-mesh screen is used for sieving, and a vacuum oven is used for drying at a temperature of 115-125° C. for 2.5-3.5 hours.

[0023] Furthermore, in step S12, when PVDF is used as a binder to prepare a lithium iron phosphate electrode, the weight ratio of lithium iron phosphate: PVDF: Ketjen black is 7-9:1:1; the mass fraction of the PVDF NMP solution is 1.5%-2.5%; after the coating is completed, the drying is carried out in a vacuum oven at a temperature of 115-125° C. for 11-13 hours;

[0024] When sodium alginate is used as a binder to prepare lithium iron phosphate pole pieces, the weight ratio of lithium iron phosphate: sodium alginate: Ketjen black is 7-9:1:1; the sodium alginate solution is prepared with deionized water, and the mass fraction of the sodium alginate solution is 1%-2%; after the coating is completed, the drying is carried out in a vacuum oven at a temperature of 75-85°C for 11-13 hours.

[0025] Furthermore, in step S2, the steps for preparing the positive electrode material covered with silica aerogel are specifically as follows:

[0026] S21, preparing silicon dioxide wet gel by sol-gel method;

[0027] S22, quickly coating the silicon dioxide wet gel on the lithium iron phosphate positive electrode;

[0028] S23, leaving the mixture to stand until the wet silica gel solidifies to obtain a positive electrode material covered with silica aerogel.

[0029] Furthermore, in step 21, the specific method for preparing the silicon dioxide wet gel by the sol-gel method is:

[0030] ① Add tetraethyl orthosilicate, ethanol and deionized water into a reaction container and mix them evenly, wherein the volume ratio of tetraethyl orthosilicate, ethanol and deionized water is 0.8-1.2:1.8-2.2:0.2-0.4; obtain a mixed solution;

[0031] ② The mixed solution in step ① is adjusted to a pH of 4-5 with a diluted hydrochloric acid solution;

[0032] ③ Seal the reaction vessel and stir at 22-28°C for 5.5-6.5h to fully hydrolyze ethyl orthosilicate;

[0033] ④ Keep stirring and add ammonia water to adjust the pH to 6-8 to obtain an aerogel precursor solution; small silica particles and a gel-like substance will quickly form in the aerogel precursor solution after adding ammonia water, that is, a silica wet gel is obtained.

[0034] Furthermore, in the step S22, the coating thickness of the silicon dioxide wet gel on the lithium iron phosphate positive electrode is 22-28 μm.

[0035] Furthermore, in step S3, the method of filling the organic monomer into the pores of the silica aerogel is:

[0036] S31, dissolving polyethylene glycol diacrylate, pentaerythritol tetrakis(3-mercaptopropionic acid), succinonitrile, and lithium bis(trifluoromethanesulfonyl imide) in anhydrous ethanol at a mass ratio of 2.5-3.5:0.4-0.6:1.5-7:3.5-5 to obtain a mixed solution, wherein the mass fraction of the solute in the mixed solution is 20-25%;

[0037] S32, immersing the positive electrode material covered with the silica aerogel obtained in step S2 in the mixed solution prepared in step S31; evaporating ethanol at a temperature of 55-65°C for 25-30 minutes. During the evaporation of ethanol, polyethylene glycol diacrylate, pentaerythritol tetrakis(3-mercaptopropionic acid), succinonitrile and lithium bis(trifluoromethanesulfonyl imide) are gradually concentrated and filled into the pores of the silica aerogel.

[0038] Furthermore, in step S3, the photocatalytic polymerization reaction is carried out by irradiating with a 1800-2200W ultraviolet lamp for 55-65S.

[0039] The present invention provides an integrated positive electrode and gel electrolyte prepared by the above-mentioned preparation method.

[0040] Based on the above technical solution, the embodiments of the present invention can at least produce the following technical effects:

[0041] (1) The method for preparing the integrated positive electrode and gel electrolyte provided by the present invention greatly increases the contact area between the electrode and the electrolyte, and reduces the interface impedance from 600 ohms to 300 ohms, greatly reducing the interface impedance and improving the performance of the solid-state lithium-ion battery, truly solving the interface contact problem of the solid electrolyte, and can be used for industrial production;

[0042] (2) The preparation method of the integrated positive electrode and gel electrolyte provided by the present invention has a simple process for assembling a battery of the integrated positive electrode, gel electrolyte and lithium sheet. It only needs to package the integrated positive electrode, electrolyte and lithium sheet without the need for liquid injection, standing, vacuuming and other processes.

[0043] (3) The preparation method of the integrated positive electrode and gel electrolyte provided by the present invention, the obtained integrated positive electrode and gel electrolyte, because the surface of the silica aerogel is rich in hydroxyl groups, is conducive to the dissociation and migration of lithium ions. After the organic electrolyte is filled into the aerogel skeleton, it still remains in an amorphous state without obvious crystallization phenomenon. The mixed electrolyte has good thermal stability. The thermogravimetric test results show that the starting temperature of weight loss is 350°C, which is much higher than the temperature of 155°C of conventional electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 This is a scanning electron microscope test image of an integrated positive electrode and a gel electrolyte (binder is PVDF) with a silica aerogel as the skeleton in Example 1 of the present invention;

[0045] Figure 2 for Figure 1 A partial enlarged view of

[0046] Figure 3 This is a scanning electron microscope test image of an integrated positive electrode and a gel electrolyte (the binder is sodium alginate) with a silica aerogel as the skeleton in Example 2 of the present invention;

[0047] Figure 4 The 0.1C and 0.2C charge and discharge curves of the all-solid-state battery assembled with the integrated positive electrode and gel electrolyte obtained in Example 1 of the present invention at room temperature. DETAILED DESCRIPTION

[0048] 1. Preparation Example

[0049] Embodiment 1:

[0050] A method for preparing an integrated positive electrode and gel electrolyte comprises the following steps:

[0051] S1. preparing a lithium iron phosphate positive electrode;

[0052] S11, sieving the lithium iron phosphate powder with a 450-mesh sieve to remove lithium iron phosphate particles with large particle sizes, and then drying the lithium iron phosphate powder obtained after the sieving until it is completely dehydrated, and the drying is carried out in a vacuum oven at a temperature of 120° C. for 3 hours;

[0053] S12, prepare lithium iron phosphate pole piece, using PVDF as adhesive:

[0054] PVDF is configured into a PVDF NMP solution, the mass fraction of the PVDF NMP solution is 2%; it is mixed with the lithium iron phosphate powder and Ketjen black dried in step S11 in a ball mill, the weight ratio of the lithium iron phosphate: PVDF: Ketjen black is 8:1:1; after ball milling, a positive electrode slurry is obtained; aluminum foil is spread on an adjustable automatic coater, the positive electrode slurry is poured on the aluminum foil, and the slurry is evenly scraped on the aluminum foil using a scraper, and the thickness of the positive electrode slurry coating is adjusted to 300 microns by the height of the scraper. After scraping, it is transferred to a vacuum oven for drying; the drying is carried out in a vacuum oven at a temperature of 120°C for 12 hours; after drying, the dried electrode piece is taken out and cut into discs, that is, a lithium iron phosphate positive electrode with a binder of PVDF is obtained; the electrode piece cut into discs is weighed, and the active material loading is calculated for standby use;

[0055] S2, in situ synthesizing a silica aerogel skeleton on the lithium iron phosphate positive electrode to obtain a positive electrode material covered with silica aerogel; specifically comprising the following sub-steps:

[0056] S21, preparing silicon dioxide wet gel by sol-gel method;

[0057] ① Add tetraethyl orthosilicate, ethanol and deionized water into a reaction container and mix them evenly, wherein the volume ratio of tetraethyl orthosilicate, ethanol and deionized water is 1:2:0.3; and obtain a mixed solution;

[0058] ② The mixed solution in step ① is adjusted to a pH of 4-5 with a diluted hydrochloric acid solution;

[0059] ③ Seal the reaction vessel and stir at 25°C for 6 hours to fully hydrolyze ethyl orthosilicate;

[0060] ④ Keep stirring, add ammonia water to adjust the pH to 7, and obtain an aerogel precursor solution; after adding ammonia water, small silica particles and a gel-like substance will quickly form in the aerogel precursor solution, that is, a silica wet gel will be obtained;

[0061] S22, quickly coating the silicon dioxide wet gel on the lithium iron phosphate positive electrode, wherein the coating thickness of the silicon dioxide wet gel on the lithium iron phosphate positive electrode is 25 μm

[0062] S23, standing still, and obtaining a positive electrode material covered with silica aerogel after the silica wet gel solidifies;

[0063] S3, filling the pores of the silica aerogel with organic monomers, using ultraviolet light to cause a photocatalytic polymerization reaction of the organic monomers, and wrapping the lithium iron phosphate positive electrode and the silica aerogel skeleton after the organic monomers are polymerized and cross-linked to obtain an integrated positive electrode and gel electrolyte with the silica aerogel as the skeleton, which specifically includes the following sub-steps:

[0064] S31, dissolving polyethylene glycol diacrylate, pentaerythritol tetrakis(3-mercaptopropionic acid), succinonitrile, and lithium bis(trifluoromethanesulfonyl imide) in anhydrous ethanol at a mass ratio of 3:0.5:2:4 to obtain a mixed solution, wherein the mass fraction of the solute in the mixed solution is 25%;

[0065] S32, immersing the positive electrode material covered with the silica aerogel obtained in step S2 in the mixed solution prepared in step S31; evaporating ethanol at a temperature of 60° C. for 30 minutes, during the evaporation of ethanol, polyethylene glycol diacrylate, pentaerythritol tetrakis(3-mercaptopropionic acid), succinonitrile and lithium bis(trifluoromethanesulfonyl imide) are gradually concentrated and filled into the pores of the silica aerogel;

[0066] S33. A 2000W ultraviolet lamp is used to irradiate for 60S to initiate a photocatalytic polymerization reaction of polyethylene glycol diacrylate, pentaerythritol tetrakis(3-mercaptopropionate), succinonitrile, and lithium bis(trifluoromethanesulfonyl imide). After the polyethylene glycol diacrylate, pentaerythritol tetrakis(3-mercaptopropionate), succinonitrile, and lithium bis(trifluoromethanesulfonyl imide) are polymerized and cross-linked, the lithium iron phosphate positive electrode is wrapped with a silica aerogel skeleton to obtain an integrated positive electrode and gel electrolyte with a silica aerogel as the skeleton.

[0067] Embodiment 2:

[0068] The difference from Example 1 is:

[0069] In step S12, sodium alginate is used as a binder to prepare a lithium iron phosphate electrode:

[0070] Sodium alginate is prepared into a sodium alginate solution, wherein the sodium alginate solution is prepared with deionized water, and the mass fraction of the sodium alginate solution is 1.5%; the sodium alginate is mixed with the lithium iron phosphate powder and Ketjen black dried in step S11 in a ball mill, wherein the weight ratio of the lithium iron phosphate: sodium alginate: Ketjen black is 8:1:1, and a positive electrode slurry is obtained after ball milling; an aluminum foil is spread on an adjustable automatic coater, the positive electrode slurry is poured on the aluminum foil, and the slurry is evenly scraped on the aluminum foil using a scraper, and the thickness of the slurry coating is adjusted to 450 microns by the height of the scraper, and then dried after the scraping is completed, and the drying is carried out in a vacuum oven at a temperature of 80° C. for 12 hours; after the drying is completed, the dried electrode piece is taken out and cut into discs, i.e., a lithium iron phosphate positive electrode with a binder of sodium alginate is obtained; the electrode piece cut into discs is weighed, and the active material loading is calculated for standby use;

[0071] The other steps were the same as those in Example 1, and an integrated positive electrode and gel electrolyte with silica aerogel as the skeleton was obtained.

[0072] Embodiment 3:

[0073] A method for preparing an integrated positive electrode and gel electrolyte comprises the following steps:

[0074] S1. preparing a lithium iron phosphate positive electrode;

[0075] S11, sieving the lithium iron phosphate powder with a 450-mesh sieve to remove lithium iron phosphate particles with large particle sizes, and then drying the lithium iron phosphate powder obtained after the sieving until it is completely dehydrated, and the drying is carried out in a vacuum oven at a temperature of 125° C. for 2.5 hours;

[0076] Sieve.

[0077] S12, prepare lithium iron phosphate pole piece, using PVDF as adhesive:

[0078] PVDF is configured into a PVDF NMP solution, wherein the mass fraction of the PVDF NMP solution is 2.5%; the PVDF is mixed with the lithium iron phosphate powder and Ketjen black dried in step S11 in a ball mill, wherein the weight ratio of the lithium iron phosphate: PVDF: Ketjen black is 9:1:1; a positive electrode slurry is obtained after ball milling; an aluminum foil is spread on an adjustable automatic coater, the positive electrode slurry is poured on the aluminum foil, and the slurry is evenly scraped on the aluminum foil using a scraper, and the thickness of the positive electrode slurry coating is adjusted to 400 microns by using the height of the scraper, and after the scraping is completed, it is transferred to a vacuum oven for drying; the drying is carried out in a vacuum oven at a temperature of 125° C. for 11 hours, and after the drying is completed, the dried electrode piece is taken out and cut into discs, i.e., a lithium iron phosphate positive electrode with a binder of PVDF is obtained; the electrode piece cut into discs is weighed, and the active material loading is calculated for standby use;

[0079] S2, in situ synthesizing a silica aerogel skeleton on the lithium iron phosphate positive electrode to obtain a positive electrode material covered with silica aerogel; specifically comprising the following sub-steps:

[0080] S21, preparing silicon dioxide wet gel by sol-gel method;

[0081] ① Adding tetraethyl orthosilicate, ethanol and deionized water into a reaction container and mixing them evenly, wherein the volume ratio of tetraethyl orthosilicate, ethanol and deionized water is 0.8:2.2:0.4; obtaining a mixed solution;

[0082] ② The mixed solution in step ① is adjusted to pH 5 with a diluted hydrochloric acid solution;

[0083] ③ Seal the reaction vessel and stir at 28°C for 5.5h to fully hydrolyze ethyl orthosilicate;

[0084] ④ Keep stirring, add ammonia water to adjust the pH to 8, and obtain an aerogel precursor solution; after adding ammonia water, small silica particles and a gel-like substance will quickly form in the aerogel precursor solution, that is, a silica wet gel will be obtained;

[0085] S22, quickly coating the silicon dioxide wet gel on the lithium iron phosphate positive electrode;

[0086] The coating thickness of the silicon dioxide wet gel on the lithium iron phosphate positive electrode is 28 μm

[0087] S23, standing still and waiting for the silicon dioxide wet gel to solidify to obtain a positive electrode material covered with silicon dioxide aerogel;

[0088] S3, filling the pores of the silica aerogel with organic monomers, using ultraviolet light to cause a photocatalytic polymerization reaction of the organic monomers, and wrapping the lithium iron phosphate positive electrode and the silica aerogel skeleton after the organic monomers are polymerized and cross-linked to obtain an integrated positive electrode and gel electrolyte with the silica aerogel as the skeleton, which specifically includes the following sub-steps:

[0089] S31, dissolving polyethylene glycol diacrylate, pentaerythritol tetrakis(3-mercaptopropionic acid), succinonitrile, and lithium bis(trifluoromethanesulfonyl imide) in anhydrous ethanol at a mass ratio of 3.5:0.4:2.5:3.5 to obtain a mixed solution, wherein the mass fraction of the solute in the mixed solution is 23%;

[0090] S32, immersing the positive electrode material covered with the silica aerogel obtained in step S2 in the mixed solution prepared in step S31; evaporating ethanol at a temperature of 65° C. for 25 min, during the evaporation of ethanol, polyethylene glycol diacrylate, pentaerythritol tetrakis(3-mercaptopropionic acid), succinonitrile and lithium bis(trifluoromethanesulfonyl imide) are gradually concentrated and filled into the pores of the silica aerogel;

[0091] S33. A 2200W ultraviolet lamp is used to irradiate for 55S to initiate a photocatalytic polymerization reaction of polyethylene glycol diacrylate, pentaerythritol tetrakis(3-mercaptopropionate), succinonitrile, and lithium bis(trifluoromethanesulfonyl imide). After the polyethylene glycol diacrylate, pentaerythritol tetrakis(3-mercaptopropionate), succinonitrile, and lithium bis(trifluoromethanesulfonyl imide) are polymerized and cross-linked, the lithium iron phosphate positive electrode is wrapped with a silica aerogel skeleton to obtain an integrated positive electrode and gel electrolyte with a silica aerogel as the skeleton.

[0092] Embodiment 4:

[0093] The difference from Example 3 is that:

[0094] In step S12, sodium alginate is used as a binder to prepare a lithium iron phosphate electrode:

[0095] Sodium alginate is prepared into a sodium alginate solution, wherein the sodium alginate solution is prepared with deionized water, and the mass fraction of the sodium alginate solution is 2%; the sodium alginate is mixed with the lithium iron phosphate powder and Ketjen black dried in step S11 in a ball mill, wherein the weight ratio of the lithium iron phosphate: sodium alginate: Ketjen black is 9:1:1, and a positive electrode slurry is obtained after ball milling; an aluminum foil is spread on an adjustable automatic coater, the positive electrode slurry is poured on the aluminum foil, and the slurry is evenly scraped on the aluminum foil using a scraper, and the thickness of the slurry coating is adjusted to 600 microns by the height of the scraper, and then dried after the scraping is completed, and the drying is carried out in a vacuum oven at a temperature of 85° C. for 11 hours; after the drying is completed, the dried electrode piece is taken out and cut into discs, so as to obtain a lithium iron phosphate positive electrode with a binder of sodium alginate; the electrode piece cut into discs is weighed, and the active material loading is calculated for standby use;

[0096] The rest is the same as in Example 3, and an integrated positive electrode and gel electrolyte with silica aerogel as the skeleton is obtained.

[0097] Embodiment 5:

[0098] A method for preparing an integrated positive electrode and gel electrolyte comprises the following steps:

[0099] S1. preparing a lithium iron phosphate positive electrode;

[0100] S11, sieving the lithium iron phosphate powder with a 450-mesh sieve to remove lithium iron phosphate particles with large particle sizes, and then drying the lithium iron phosphate powder obtained after the sieving until it is completely dehydrated, and the drying is carried out in a vacuum oven at a temperature of 115° C. for 3.5 hours;

[0101] S12, prepare lithium iron phosphate pole piece, using PVDF as adhesive:

[0102] PVDF is configured into a PVDF NMP solution, the mass fraction of the PVDF NMP solution is 1.5%; it is mixed with the lithium iron phosphate powder and Ketjen black dried in step S11 in a ball mill, the weight ratio of the lithium iron phosphate: PVDF: Ketjen black is 7:1:1; after ball milling, a positive electrode slurry is obtained; aluminum foil is spread on an adjustable automatic coater, the positive electrode slurry is poured on the aluminum foil, and the slurry is evenly scraped on the aluminum foil using a scraper, and the thickness of the positive electrode slurry coating is adjusted to 100 microns by the height of the scraper. After scraping, it is transferred to a vacuum oven for drying, and the drying is carried out in a vacuum oven at a temperature of 115°C for 13 hours; after drying, the dried electrode piece is taken out and cut into discs, that is, a lithium iron phosphate positive electrode with a binder of PVDF is obtained; the electrode piece cut into discs is weighed, and the active material loading is calculated for standby use;

[0103] S2, in situ synthesizing a silica aerogel skeleton on the lithium iron phosphate positive electrode to obtain a positive electrode material covered with silica aerogel; specifically comprising the following sub-steps:

[0104] S21, preparing silicon dioxide wet gel by sol-gel method;

[0105] ① Add tetraethyl orthosilicate, ethanol and deionized water into a reaction container and mix them evenly, wherein the volume ratio of tetraethyl orthosilicate, ethanol and deionized water is 1.2:2:0.3; and obtain a mixed solution;

[0106] ② The mixed solution in step ① is adjusted to pH 4 with a diluted hydrochloric acid solution;

[0107] ③ Seal the reaction vessel and stir at 22°C for 6.5h to fully hydrolyze ethyl orthosilicate;

[0108] ④ Keep stirring, add ammonia water to adjust the pH to 6, and obtain an aerogel precursor solution; after adding ammonia water, small silica particles and a gel-like substance will quickly form in the aerogel precursor solution, that is, a silica wet gel will be obtained;

[0109] S22, quickly coating the silicon dioxide wet gel on the lithium iron phosphate positive electrode;

[0110] The coating thickness of the silicon dioxide wet gel on the lithium iron phosphate positive electrode is 22 μm

[0111] S23, standing still and waiting for the silicon dioxide wet gel to solidify to obtain a positive electrode material covered with silicon dioxide aerogel;

[0112] S3, filling the pores of the silica aerogel with organic monomers, using ultraviolet light to cause a photocatalytic polymerization reaction of the organic monomers, and wrapping the lithium iron phosphate positive electrode and the silica aerogel skeleton after the organic monomers are polymerized and cross-linked to obtain an integrated positive electrode and gel electrolyte with the silica aerogel as the skeleton, which specifically includes the following sub-steps:

[0113] S31, dissolving polyethylene glycol diacrylate, pentaerythritol tetrakis(3-mercaptopropionic acid), succinonitrile, and lithium bis(trifluoromethanesulfonyl imide) in anhydrous ethanol at a mass ratio of 2.5:0.6:1.5:3.5 to obtain a mixed solution, wherein the mass fraction of the solute in the mixed solution is 20%;

[0114] S32, immersing the positive electrode material covered with the silica aerogel obtained in step S2 in the mixed solution prepared in step S31; evaporating ethanol at a temperature of 55° C. for 30 minutes, during the evaporation of ethanol, polyethylene glycol diacrylate, pentaerythritol tetrakis(3-mercaptopropionic acid), succinonitrile and lithium bis(trifluoromethanesulfonyl imide) are gradually concentrated and filled into the pores of the silica aerogel;

[0115] S33. An 1800W ultraviolet lamp is used to irradiate for 65S to initiate a photocatalytic polymerization reaction of polyethylene glycol diacrylate, pentaerythritol tetrakis(3-mercaptopropionate), succinonitrile, and lithium bis(trifluoromethanesulfonyl imide). After the polyethylene glycol diacrylate, pentaerythritol tetrakis(3-mercaptopropionate), succinonitrile, and lithium bis(trifluoromethanesulfonyl imide) are polymerized and cross-linked, the lithium iron phosphate positive electrode is wrapped with a silica aerogel skeleton to obtain an integrated positive electrode and gel electrolyte with a silica aerogel as the skeleton.

[0116] Embodiment 6:

[0117] The difference from Example 5 is:

[0118] In step S12, sodium alginate is used as a binder to prepare a lithium iron phosphate electrode:

[0119] Sodium alginate is prepared into a sodium alginate solution, wherein the sodium alginate solution is prepared with deionized water, and the mass fraction of the sodium alginate solution is 1%; the sodium alginate is mixed with the lithium iron phosphate powder and Ketjen black dried in step S11 in a ball mill, wherein the weight ratio of the lithium iron phosphate: sodium alginate: Ketjen black is 7:1:1, and a positive electrode slurry is obtained after ball milling; an aluminum foil is spread on an adjustable automatic coater, and the positive electrode slurry is poured on the aluminum foil, and the slurry is evenly scraped on the aluminum foil using a scraper, and the thickness of the slurry coating is adjusted by 300 microns using the height of the scraper, and then dried after the scraping is completed, and the drying is carried out in a vacuum oven at a temperature of 75° C. for 13 hours; after the drying is completed, the dried electrode piece is taken out and cut into discs, i.e., a lithium iron phosphate positive electrode with a binder of sodium alginate is obtained; the electrode piece cut into discs is weighed, and the active material loading is calculated for standby use;

[0120] The rest is the same as in Example 5, and an integrated positive electrode and gel electrolyte with silica aerogel as the skeleton is obtained.

[0121] Embodiment 7:

[0122] The difference from Example 1 is:

[0123] In step S31, the mass ratio of lithium bis(trifluoromethanesulfonyl)imide to succinonitrile is 1:2;

[0124] The other steps were the same as those in Example 1, and an integrated positive electrode and gel electrolyte with silica aerogel as the skeleton was obtained.

[0125] Embodiment 8:

[0126] The difference from Example 1 is:

[0127] In step S31, the mass ratio of lithium bis(trifluoromethanesulfonyl)imide to polyethylene glycol diacrylate is 2:1;

[0128] The other steps were the same as those in Example 1, and an integrated positive electrode and gel electrolyte with silica aerogel as the skeleton was obtained.

[0129] 2. Experimental Examples

[0130] 1. Metallographic examination was performed on the integrated positive electrode and gel electrolyte with silica aerogel as the skeleton obtained in Example 1 and Example 2.

[0131] Test results such as Figure 1 , Figure 2 and Figure 3 As shown, Figure 1 and Figure 2 This is a metallographic image of the integrated positive electrode and gel electrolyte (binder is PVDF) with silica aerogel as the skeleton in Example 1; Figure 3 This is a metallographic picture of the integrated positive electrode and gel electrolyte (the binder is sodium alginate) with silica aerogel as the skeleton in Example 2.

[0132] 2. Electrical performance test and evaluation of the integrated positive electrode and gel electrolyte with silica aerogel as the skeleton prepared in Examples 1-8

[0133] (1) Simulate symmetrical blocking cell assembly, using two stainless steel sheets to sandwich an electrolyte membrane to form a sandwich structure SS / AOES / SS, which is mainly used to test the ionic conductivity of the electrolyte;

[0134] ①Test method

[0135] The polymer electrolyte membrane with aerogel skeleton was prepared. The integrated positive electrode with silica aerogel as the skeleton prepared in Example 1-8 and the gel electrolyte were sandwiched between two stainless steel sheets to assemble into a SS / AOES / SS sandwich structure, and packaged in a CR2025 button battery shell. After the assembly was completed, it was kept warm at 60°C for 3h to ensure close contact between the AOES and the stainless steel sheet, and then cooled to room temperature for AC impedance testing in the frequency range of 0.1 to 10 6 Hz, with an amplitude of 5mV. The AC impedance spectrum of AOES is obtained, and the impedance R is read from the intersection of the oblique line and the horizontal axis in the figure. The contact area S between the polymer electrolyte and the stainless steel sheet is calculated by the surface area of ​​the stainless steel sheet. The ionic conductivity of AOES at room temperature is calculated by the formula σ=L / RS.

[0136] ②The test results are shown in Table 2 below:

[0137] Table 1 Ionic conductivity of electrolytes

[0138] The thickness of the electrolyte membrane is 120 microns Example 1 <![CDATA[2.6×10 -5 S cm -1 ]]> Example 2 <![CDATA[6.5×10 -5 S cm -1 ]]> Example 3 <![CDATA[7.3×10 -5 S cm -1 ]]> Example 4 <![CDATA[8.1×10 -5 S cm -1 ]]> Example 5 <![CDATA[5.2×10 -5 S cm -1 ]]> Example 6 <![CDATA[8×10 -5 S cm -1 ]]> Example 7 <![CDATA[4.4×10 -4 S cm -1 ]]> Example 8 <![CDATA[9.7×10 -5 S cm -1 ]]>

[0139] (2) Simulating the assembly of a semi-blocked asymmetric battery, an electrolyte membrane was prepared using the integrated positive electrode and gel electrolyte with the silica aerogel prepared in Examples 1-8 as the skeleton, and a stainless steel sheet and a lithium sheet were respectively formed on both sides of the electrolyte membrane, mainly used to test the electrochemical stability of the electrolyte;

[0140] ①Test method:

[0141] Linear sweep voltammetry (LSV) was used to test the electrochemical stability of the electrolyte. A Li / AOES / SS semi-blocked battery cell was assembled with a test range of 0-6 V and a scan rate of 5 mV / s.

[0142] ②The test results are shown in Table 2 below:

[0143] Table 2 Electrochemical stability

[0144]

[0145] (3) Button cell assembly: The integrated positive electrode with the silica aerogel as the skeleton and the gel electrolyte prepared in Examples 1-8 were cut into discs with a diameter of 16 mm and directly assembled with the lithium sheet in a CR2025 button cell shell to test the electrochemical properties of the battery;

[0146] ①Test method:

[0147] The constant current charge and discharge test was carried out using the BTS battery test system of Shenzhen Neware Company. The test temperature was kept constant at 25°C, and the charge and discharge cut-off voltages were 3.85V and 2.5V respectively.

[0148] ②The test results are shown in Table 3 below:

[0149] Table 3 Electrochemical performance

[0150] 0,1C 0,2C 0.5C 1C Example 1 146mAh / g 118mAh / g 20mAh / g 10mAh / g Example 2 148mAh / g 125mAh / g 78mAh / g 44mAh / g Example 3 152mAh / g 130mAh / g 83mAh / g 46mAh / g Example 4 153mAh / g 132mAh / g 90mAh / g 45mAh / g Example 5 142mAh / g 122mAh / g 75mAh / g 42mAh / g Example 6 151mAh / g 131mAh / g 96mAh / g 63mAh / g Example 7 161mAh / g 146mAh / g 123mAh / g 98mAh / g Example 8 154mAh / g 130mAh / g 97mAh / g 66mAh / g

[0151] (4) Interface impedance:

[0152] ①Test method:

[0153] The prepared integrated electrode and electrolyte material was cut into discs with a diameter of 16 mm and directly assembled with the lithium sheet in a CR2025 button battery case for AC impedance testing in the frequency range of 0.1 to 10 6 Hz, amplitude 5mV. The obtained data were fitted and analyzed to obtain the interface impedance.

[0154] ②The test results are shown in Table 4 below:

[0155] Table 4 Interface impedance

[0156]

[0157]

[0158] It can be seen from Table 4 that the interface impedance between the integrated positive electrode prepared in Examples 1-8 of the present invention and the gel electrolyte is much lower than the interface impedance of the conventional electrolyte (600 ohms).

[0159] (5) Testing the thermal stability of the integrated positive electrode and gel electrolyte prepared in Examples 1-8

[0160] ①Test method:

[0161] The thermal stability tester was PerkinElmer Simultaneous Thermal Analyzer (STA-8000) with nitrogen atmosphere. The test range was from room temperature to 800°C with a heating rate of 5°C / min.

[0162] ②The test results are shown in Table 5 below:

[0163] Table 5 Thermal stability

[0164] Weight loss starting temperature Example 1 367℃ Example 2 352℃ Example 3 345℃ Example 4 350℃ Example 5 360℃ Example 6 350℃ Example 7 336℃ Example 8 352℃

[0165] As can be seen from Table 5, the thermogravimetric test results of the integrated positive electrode and gel electrolyte prepared in Examples 1-8 of the present invention show that the weight loss starting temperature is 350°C, which is much higher than the temperature of 155°C of the conventional electrolyte, indicating that the integrated positive electrode and gel electrolyte prepared in Examples 1-8 of the present invention have good thermal stability.

Claims

1. A method for preparing an integrated positive electrode and a gel electrolyte, characterized in that: The steps include: S1, preparing a lithium iron phosphate positive electrode; S2, in situ synthesizing a silica aerogel skeleton on the lithium iron phosphate positive electrode to obtain a positive electrode material covered with silica aerogel; S3. Filling organic monomers into the pores of silica aerogel, using ultraviolet light to cause photocatalytic polymerization of the organic monomers, and after the organic monomers are polymerized and cross-linked, wrapping the lithium iron phosphate positive electrode and the silica aerogel skeleton to obtain an integrated positive electrode and gel electrolyte with the silica aerogel as the skeleton.

2. The method for preparing an integrated positive electrode and gel electrolyte according to claim 1, characterized in that: In step S1, the steps for preparing the lithium iron phosphate positive electrode are specifically as follows: S11, sieving the lithium iron phosphate powder with a sieve to remove lithium iron phosphate particles with large particle sizes, and then drying the lithium iron phosphate powder obtained after the sieving until it is completely dehydrated; S12, prepare lithium iron phosphate pole piece, and use PVDF or sodium alginate as adhesive: ① When using PVDF as a binder to prepare lithium iron phosphate pole pieces PVDF is configured into a PVDF NMP solution, and the solution is mixed with the lithium iron phosphate powder and Ketjen black dried in step S11 in a ball mill to obtain a positive electrode slurry after ball milling; aluminum foil is spread on an adjustable automatic coater, the positive electrode slurry is poured on the aluminum foil, and the slurry is evenly scraped on the aluminum foil using a scraper, and the thickness of the positive electrode slurry coating is adjusted to 100-400 microns according to the height of the scraper, and after the scraping is completed, it is transferred to a vacuum oven for drying; After drying, the dried electrode is taken out and cut into discs, thus obtaining a lithium iron phosphate positive electrode with PVDF as the binder; the electrode cut into discs is weighed, and the active material loading is calculated for later use; ② When using sodium alginate as a binder to prepare lithium iron phosphate electrodes Sodium alginate is prepared into a sodium alginate solution, and the solution is mixed with the lithium iron phosphate powder and Ketjen black dried in step S11 in a ball mill to obtain a positive electrode slurry after ball milling; aluminum foil is spread on an adjustable automatic coater, the positive electrode slurry is poured on the aluminum foil, and the slurry is evenly scraped on the aluminum foil using a scraper, and the thickness of the slurry coating is adjusted to 300-600 microns according to the height of the scraper, and drying is performed after scraping; After drying, the dried electrode is taken out and cut into discs, thus obtaining a lithium iron phosphate positive electrode with sodium alginate as the binder; the electrode cut into discs is weighed, and the active material loading is calculated for later use.

3. The method for preparing an integrated positive electrode and gel electrolyte according to claim 2, characterized in that: In the step S11, a 450-mesh screen is used for sieving, and a vacuum oven is used for drying at a temperature of 115-125° C. for 2.5-3.5 hours.

4. The method for preparing an integrated positive electrode and gel electrolyte according to claim 2, characterized in that: In the step S12, when PVDF is used as a binder to prepare a lithium iron phosphate electrode, the weight ratio of lithium iron phosphate: PVDF: Ketjen black is 7-9:1:1; the mass fraction of the PVDF NMP solution is 1.5%-2.5%; after the coating is completed, the drying is carried out in a vacuum oven at a temperature of 115-125° C. for 11-13 hours; When sodium alginate is used as a binder to prepare lithium iron phosphate pole pieces, the weight ratio of lithium iron phosphate: sodium alginate: Ketjen black is 7-9:1:1; the sodium alginate solution is prepared with deionized water, and the mass fraction of the sodium alginate solution is 1%-2%; after the coating is completed, the drying is carried out in a vacuum oven at a temperature of 75-85°C for 11-13 hours.

5. The method for preparing an integrated positive electrode and gel electrolyte according to claim 1, characterized in that: In step S2, the steps for preparing the positive electrode material covered with silica aerogel are specifically as follows: S21, preparing silicon dioxide wet gel by sol-gel method; S22, quickly coating the silicon dioxide wet gel on the lithium iron phosphate positive electrode; S23, leaving the mixture to stand until the wet silica gel solidifies to obtain a positive electrode material covered with silica aerogel.

6. The method for preparing an integrated positive electrode and gel electrolyte according to claim 5, characterized in that: In step 21, the specific method for preparing silicon dioxide wet gel by sol-gel method is: ① Add tetraethyl orthosilicate, ethanol and deionized water into a reaction container and mix them evenly, wherein the volume ratio of tetraethyl orthosilicate, ethanol and deionized water is 0.8-1.2:1.8-2.2:0.2-0.4; obtain a mixed solution; ② The mixed solution in step ① is adjusted to a pH of 4-5 with a diluted hydrochloric acid solution; ③ Seal the reaction vessel and stir at 22-28°C for 5.5-6.5h to fully hydrolyze ethyl orthosilicate; ④ Keep stirring and add ammonia water to adjust the pH to 6-8 to obtain an aerogel precursor solution; small silica particles and a gel-like substance will quickly form in the aerogel precursor solution after adding ammonia water, that is, a silica wet gel is obtained.

7. The method for preparing an integrated positive electrode and gel electrolyte according to claim 5, characterized in that: In the step S22, the coating thickness of the silicon dioxide wet gel on the lithium iron phosphate positive electrode is 22-28 μm.

8. The method for preparing an integrated positive electrode and gel electrolyte according to claim 1, characterized in that: In step S3, the method of filling the organic monomer into the pores of the silica aerogel is: S31, dissolving polyethylene glycol diacrylate, pentaerythritol tetrakis(3-mercaptopropionic acid), succinonitrile, and lithium bis(trifluoromethanesulfonyl imide) in anhydrous ethanol at a mass ratio of 2.5-3.5:0.4-0.6:1.5-7:3.5-5 to obtain a mixed solution, wherein the mass fraction of the solute in the mixed solution is 20-25%; S32, immersing the positive electrode material covered with the silica aerogel obtained in step S2 in the mixed solution prepared in step S31; evaporating ethanol at a temperature of 55-65°C for 25-30 minutes. During the evaporation of ethanol, polyethylene glycol diacrylate, pentaerythritol tetrakis(3-mercaptopropionic acid), succinonitrile and lithium bis(trifluoromethanesulfonyl imide) are gradually concentrated and filled into the pores of the silica aerogel.

9. The method for preparing an integrated positive electrode and gel electrolyte according to claim 1, characterized in that: In step S3, the photocatalytic polymerization reaction is carried out by irradiating with a 1800-2200W ultraviolet lamp for 55-65S.

10. An integrated positive electrode and gel electrolyte prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • An integrated solid electrolyte-positive electrode assembly, its preparation method and application

    CN114171784B

  • A solid electrolyte-electrode integrated diaphragm and preparation method thereof

    CN114171848B

  • Cross-linked network SiO2 composite single-ion conductor electrolyte, and preparation method and application thereof

    CN112952202A

  • Carbon aerogel-based cathodes for lithium-air batteries

    CN113711422A